Social segregation, misperceptions, and emergent cyclical choice patterns - Daniel Mayerhoffer; Jan Schulz-Gebhard (Bamberg University, Bamberg Economic Research Group (BERG), 2023)
This paper examines the puzzle of why economic inequality has not resulted in political countermeasures to mitigate it, and proposes that the reason is due to misperceptions of economic inequality caused by segregation in social networks. We model taxation and voting behavior with an exponential income distribution and a Random Geometric Graph-type model to represent homophily, which leads to people perceiving their own income rank and income to be close to the middle. We find that people base their beliefs about mean income on a compound of the true mean and their local perception in the network, and that higher homophily causes lower implemented tax rates, which explains why redistribution preferences appear decoupled from actual inequality. In a dynamic extension, we also demonstrate that a rich set of dynamic behaviours can emerge from rational updating beliefs about efficiency. Misperceptions not only decrease redistribution in a static setting, they also hinder agents from adapting and learning towards the unbiased tax rate in a dynamic sense. As policy implications, we suggest two measures to counteract this: educating people about the actual income distribution and promoting diversity to reduce homophily.
Keywords: 330; Inequality; redistribution; perception; bias; networks